Pendidikan Adaptif di Masa Covid-19 dengan Program MDR - Diah Retno Widowati; Farid Noor Romadlon; Norita Prasetya Wardhani (Universitas Muria Kudus, 2022)
The government has always tried to achieve equal education for all Indonesian people. During the Covid-19 pandemic, many educators, especially from remote areas, objected to the implementation of online-based learning for various reasons. Therefore, the Ministry of Education and Culture launched the Teaching From Home (MDR) program by involving various levels of society from various regions in Indonesia to jointly carry out learning for students at the Kindergarten (TK), Elementary School, and Junior High School levels. as a form of community service to the world of education. This is done to improve the literacy and numeracy skills of the students involved in it. This study aims to describe the activities carried out in the MDR program, the benefits obtained by teachers and students, obstacles during the learning process, and how to overcome these obstacles.